Pengaruh Entrepreneurial Passion dan Pendidikan Kewirausahaan Terhadap Minat Berwirausaha - Prihatini Sukmawati; Yoni Hermawan; Ai Nur Solihat (Journal of Business and Economics Research (JBE), 2026)
Entrepreneurial interest among students is an important part in supporting the creation of entrepreneurs who are able to create new jobs. However, not all students show a strong interest in the business world. This situation can be influenced by several factors, such as entrepreneurial passion and entrepreneurship education. This study aims to determine the effect of entrepreneurial passion and entrepreneurship education on entrepreneurial interest. The population in this study were students of the Faculty of Teacher Training and Education, Siliwangi University, class of 2023. The research method used was a quantitative survey. Data were collected through questionnaires distributed to 107 students using proportionate stratified random sampling. Primary data were obtained through questionnaires to respondents. Data were analyzed using multiple linear regression with SPSS 29.0. The results indicate that entrepreneurial passion and entrepreneurship education simultaneously have a positive and significant influence on entrepreneurial interest, with an F-value of 164.033 > 3.08 and a significance value of 0.001 < 0.05. Entrepreneurial passion partially has a positive and significant influence on entrepreneurial interest, with a t-value of 7.466 > 1.983 and a significance value of 0.001 < 0.05. Entrepreneurship education partially has a positive and significant influence on entrepreneurial interest, with a t-value of 4.037 > 1.983 and a significance value of 0.001 < 0.05. This study is expected to contribute to the development of entrepreneurship in higher education that is more creative, adaptive, and integrated.